How Chinese attitudes toward COVID-19 policies changed between June and early December 2022: Risk perceptions and the uses of mainstream media and WeChat - Xiao Wang (Elsevier, 2023)
Debates about China's zero-COVID policy should consider Chinese public attitudes toward COVID-19 and China's COVID-19 policies. Such attitudes can provide a theoretical account for public health crisis management and have implications for China to manage future public health crises. The present research reports on two surveys conducted in mainland China in June (N = 460) and early December 2022 (N = 450) to examine the changing COVID-19 risk perceptions and policy attitudes. Results showed that the participants' perception of the severity of COVID-19, perceived health consequences of a COVID-19 policy, and fear predicted their policy attitudes. In contrast, perceived disruption to the economy and daily lives was a weak predictor of Chinese attitudes toward a COVID policy. Furthermore, mainstream media use was positively associated with favorable attitudes toward the COVID-19 policy backed by the government (i.e., zero-COVID in June and relaxing restrictions in December). On the other hand, the uses of WeChat positively predicted favorable attitudes toward the alternatives to the government's approach. The results indicate the need to address public health concerns and employ the mainstream media in China for public health communication.